Oropharyngeal carriage and lower airway colonisation/infection in 45 tracheotomised children. Issue 12 (1st December 2002) - Morar, P; Singh, V; Makura, Z; Jones, A S; Baines, P B; Selby, A; Sarginson, R; Hughes, J; van Saene, R
Abstract : Background: A study was undertaken to determine the oropharyngeal carrier state of potentially pathogenic microorganisms (PPM) and the magnitude of colonisation and infection rates of the lower airways with these PPM in children requiring long term ventilation first transtracheally and afterwards via a tracheotomy. Methods: A 5 year, prospective, observational cohort study was undertaken in 45 children (33 boys) of median age 6.4 months (range 0–180) over a 5 year period at the Royal Liverpool Children's NHS Trust of Alder Hey, a university affiliated tertiary referral centre. The children were first admitted to the 20-bed paediatric intensive care unit (PICU) and, following placement of a tracheotomy, they were transferred to a four bedded respiratory ward. The two main indications were neurological disorders and airway obstruction. All children were ventilated transtracheally for a median period of 12 days (range 0–103) and, after placement of the tracheotomy, for a similar period of 12 days (range 1–281). Surveillance cultures of the oropharynx were taken on admission to the PICU and on the day of placement of the tracheotomy. Throat swabs were taken twice weekly during ventilation, both transtracheal and via the tracheotomy. Tracheal aspirates were taken once weekly and when clinically indicated (in cases where the lower airway secretions were turbid). Results: Twenty five patients (55%) had abnormal flora, mainly aerobic Gram negative bacilli (AGNB), particularly Pseudomonas aeruginosa, while the community PPM Staphylococcus aureus was present in the oropharynx of 37% (17/45) of the study population. The lower airways were sterile in six children; the other 39 patients (87%) had a total of 82 episodes of colonisation. "Community" PPM significantly increased once the patients received a tracheotomy, independent of the number of patients enrolled, episodes of colonisation/infection, and the number of colonised/infected patients. "Hospital" PPM significantly decreased after tracheotomy only when episodes were compared. Conclusions: While P aeruginosa present in the admission flora caused primary endogenous colonisation/infection during mechanical ventilation on the PICU, S aureus not carried in the throat was responsible for the exogenous colonisation/infection once the patients had a tracheotomy. This is in sharp contrast to adult studies where exogenous infections are invariably caused by AGNB. This discrepancy may be explained by chronic underlying conditions such as diabetes, alcoholism, and chronic obstructive pulmonary disease which promote AGNB, whereas the children were recovering following tracheotomy.